Backscattered electrons from gold surface films deposited on silicon substrates: a joint experimental and computational investigation to add new potentiality to electron microscopy. (2nd August 2012) - Dapor, Maurizio; Bazzanella, Nicola; Toniutti, Laura; Miotello, Antonio; Crivellari, Michele; Gialanella, Stefano
<x xml:space="preserve">Abstract</x> This paper addresses the problem of the thickness determination of thin gold overlayers deposited on silicon bulk substrates by looking at the electron backscattering coefficient involved in scanning electron microscopy (SEM). A Monte Carlo code, used to calculate the backscattering coefficient, together with a simple experimental setup, which uses a conventional SEM, allow to determine thin film thickness (in the range 25–200 nm) with an estimated accuracy of 20%. This adds obviously new potentiality to SEM. Copyright © 2012 John Wiley & Sons, Ltd.